2022
DOI: 10.1002/adom.202200203
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Increase in the Optical Band Gap of Near‐Infrared Semiconductor Lead (II) Sulfide via the Incorporation of Amino Acids

Abstract: Incorporation of organic molecules into the crystal lattice of biominerals is one of Nature's main strategies to modify the structure, morphology, and specific physical properties of the mineral host. Inspired by this biostrategy, it is shown that several semiconductors, whose band gaps are in the ultraviolet or visible absorption spectrum, can incorporate individual amino acids (AAs) into their crystalline structures. Interestingly, such incorporation is accompanied by an increase in the optical band gap of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Similar results were found for M 115 -B 220 worms and M 115 -B 300 vesicles; in each case, the band gap was gradually decreased when the copolymer occlusion was increased (see Figures S8 and S9). It is worth noting that this finding is opposite to the results reported by others, where intracrystalline incorporation of amine acid molecules into ZnO or Cu 2 O or hybrid perovskite or PbS crystals leads to an increase in their band gap. The X-ray photoelectron spectroscopy study enables the valence band (VB) energy of each M 115 -B 1000 @Ag 3 PO 4 composite crystal to be determined (Figure c). Surprisingly, the VB of each sample remains the same, whereas the conduction band energy systematically varied (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found for M 115 -B 220 worms and M 115 -B 300 vesicles; in each case, the band gap was gradually decreased when the copolymer occlusion was increased (see Figures S8 and S9). It is worth noting that this finding is opposite to the results reported by others, where intracrystalline incorporation of amine acid molecules into ZnO or Cu 2 O or hybrid perovskite or PbS crystals leads to an increase in their band gap. The X-ray photoelectron spectroscopy study enables the valence band (VB) energy of each M 115 -B 1000 @Ag 3 PO 4 composite crystal to be determined (Figure c). Surprisingly, the VB of each sample remains the same, whereas the conduction band energy systematically varied (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Several methodologies have been utilized to modulate the band gap of various semiconductors, including controlling the chemical composition, engineering the lattice strain, and exerting size confinement. Notably, the Pokroy research group demonstrated that intracrystalline incorporation of amino acids into semiconductors, (e.g., zinc oxide (ZnO), copper­(I) oxide (Cu 2 O), lead (II) sulfide (PbS), etc.) results in an increase in the optical band gap. These interesting examples indicated that integration of “impurity” additives into semiconductor nanocrystals can engineer the physicochemical property of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of elastic strains induced by the incorporation of nucleotides and the resulting lattice distortions showed that the nucleotide-incorporating vaterite crystals undergo an internal equiaxial tensile stress of ∼30 MPa (see Supporting Information). Given that the atomic packing factor of vaterite is only ∼50.3%, 95,96 we envisage that the organic moiety of the nucleotides (i.e., the ribose ring and the nucleobase) is interstitially occluded, while the total unit cell volume is reduced due to the phosphate−Ca interactions (Figure S10). This occlusion behavior warrants an answer as to why the concentration of incorporated ATP is higher than of that CTP (and similarly, AMP is higher than that of CMP, see Figure 1), even though the adenosine molecule is bigger in size than cytosine (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Calculations of elastic strains induced by the incorporation of nucleotides and the resulting lattice distortions showed that the nucleotide-incorporating vaterite crystals undergo an internal equiaxial tensile stress of ∼30 MPa (see Supporting Information). Given that the atomic packing factor of vaterite is only ∼50.3%, , we envisage that the organic moiety of the nucleotides ( i.e. , the ribose ring and the nucleobase) is interstitially occluded, while the total unit cell volume is reduced due to the phosphate–Ca interactions (Figure S10).…”
Section: Resultsmentioning
confidence: 99%